PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA MATERI EKSRESI SISWA KELAS VIII SMP NEGERI 13 PEMATANGSIANTAR TAHUN PELAJARAN 2021/2022 - Rosenta Purba, Ika; Lihardo Hulu, Irwan; Selvia Sitohang, Dini (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study aims to determine the effect of audiovisual media use on science learning outcomes in the subject of Excretion for eighth-grade students at SMP Negeri 13 Pematangsiantar. The population in this study were 60 eighth-grade students of SMP Negeri 13 Pematangsiantar in the 2021/2022 academic year. The research sample was selected using cluster random sampling: class VIII A (Experimental Class) using audiovisual media and class VIII B (Control Class) using conventional methods. The instrument used in this study was a multiple-choice test consisting of 20 questions. Furthermore, the data obtained were analyzed to find the mean, median, mode, standard deviation, normality test, reliability, validity, and t-test. The data obtained were then analyzed using a t-test using SPSS 21. The results of this study indicate a significant effect between the use of audio-visual media on learning outcomes, with a probability value of 0.000 <α = 0.05, with a t-count of 7.688 > t-table of 1.699. Therefore, H_a is accepted and H_0 is rejected, meaning that the use of audio-visual media has an effect on the science learning outcomes of eighth-grade students at SMP Negeri 13 Pematangsiantar in the 2021/2022 academic year.